APLIKASI SISTEM INFORMASI GEOGRAFI UNTUK PEMETAAN RUTE PERJALANAN WISATA SEHARI (ONE DAY TRIP) DI KOTA BUKITTINGGI - Akram, Naufal Muhammad; Yulfa, Arie (JURNAL BUANA, 2024)
Along with the development of various tourist objects in the City of Bukittinggi and the increasing number of tourists visiting, this has led to a lack of satisfaction levels for some tourists who only have time to travel for one day (One Day Trip) in the City of Bukittinggi. The lack of tourist satisfaction levels for tourists who travel for one day (One Day Trip) in the City of Bukittinggi is caused by limited time and the affordability of the distance between one tourist destination location and another tourist destination, so that tourists do not enjoy their time to the fullest. In geography, affordability is the maximum attainable distance from one region to another. Data analysis was carried out using the Network Analysis method found in the Arcgis 10.8 application, which will produce the fastest roads/routes to get to tourist objects and process these results into a tour package. Making tour packages accompanied by maps that are intended so that tourists can take one day trips effectively, because researchers have determined the most effective routes between one object and another by conducting network analysis and making tour packages that are targeted and will not waste time .Webgis for day trips in the city of Bukittinggi which is information that can be accessed by potential tourists so they can get an overview of the packages that tourists can choose as they wish.